Early flash flood detection and avoidance system / Muhammad Aidil Aisar Mohd Yatim ... [et al.] - Mohd Yatim, Muhammad Aidil Aisar; Izahar, Muhammad Khalis Zuhri; Baharudin, Rohaiza; Abbas, Mohd Hussaini (2021)
In Malaysia, flash floods are common occurrences throughout the year and commonly occur in urbanized areas. Flash floods are mostly caused by the seasonal monsoon rain when inadequate drainage systems are unable to channel the water flow properly. The overflow of the rivers is also a major reason for occurring flash floods in the city. Late detection of this disaster may cause damage to property and infrastructure, disrupts the traffic flow, endangering human life, psychological impact to the user etc. This project is to detect a flash flood and avoidance system that aims to detect heavy rainfall followed by detecting high water level at the specified area. The system works as an indicator that will give an early warning to users and as an avoidance system that controls the flood basin gate when flood is high. This project uses Arduino UNO as a microcontroller, Ultrasonic Sensor and rain sensor as an input, and global system for mobile communication (GSM) module, buzzer, motor and liquid-crystal display (LCD) as the output of the system. A GSM is used to alert the flood condition to the user and rescue team by transmitting the water level condition measured by ultrasonic sensor. With this reliable detection system, the flash flood in urban areas can be avoided by users and authorities at an early stage. Consequently, the infrastructure damage and psychological impact to people can be minimized.